The Contribution of Entrepreneurship Lessons and PKL to Entrepreneurial Interest in SMKN Padang Students: Kontribusi Pelajaran Kewirausahaan dan PKL terhadap Minat Berwirausaha Pada Siswa SMKN Padang - Atila Yazel Aze, Hazevi; Bahri, Halimul; Oktaviani, Vina; Hadiastuti, Hadiastuti (Jurnal Pembelajaran Inovatif, 2025)
This study aims to explore how much influence entrepreneurship learning and PKL experience have on the interest of vocational students in tourism in Padang City. This research uses an ex post facto approach with a correlational research method. The population studied included all XII grade students of SMK Negeri in the field of tourism in Padang City which amounted to 725 people, with this number, 260 were sampled using proportional random sampling technique. Data collection is done through questionnaire instruments. In monitoring the instrument that needs to be done is confirmatory factor analysis (CFA). Data analysis techniques applied include descriptive analysis and multiple regression. The research findings show that: (1) entrepreneurship subjects contribute 2.9% to entrepreneurial interest and have a positive effect, (2) internship experience contributes 4.7% to student entrepreneurial interest and also have a positive effect, and (3) overall, the two variables contribute 7.9% to student entrepreneurial interest and have a positive effect.